Recoletos de Bacolod Graduate School Docuware: E-document management system - Antenor, Mariano, Jr. (Technium Social Sciences Journal, 2025)
Introduction: The RBGS (Recoletos de Bacolod Graduate School) Docuware: e-Document Management System is an application designed to automate the management of academic documents by uploading them to the system. This system provides a centralized platform for secure, efficient, and organized storage and retrieval of records so that both student and faculty documents are easily accessible. The system is specifically tailored for use within the graduate school, offering a user-friendly interface and useful features to support the institution’s document management needs. Product Descriptions: The traditional manual process of storing and retrieving documents posed significant challenges, such as inefficiency and the risk of data loss. To address these issues, RBGS (Recoletos de Bacolod Graduate School) Docuware: e-Document Management System was developed with features including centralized storage, advanced search capabilities, filename encryption, and secure backup functionality. The system allows users to upload documents exclusively in PDF format, ensuring uniformity and ease of management. Additionally, the EDMS is API-ready, enabling future integration with other systems for expanded functionality and data sharing. System Features: The RBGS (Recoletos de Bacolod Graduate School) Docuware: e-Document Management System includes features such as a keyword-based search engine, user authentication, protocol authorization to control access, and a visual dashboard for monitoring document interactions and system performance. Developed using the Rapid Application Development (RAD) methodology, the system undergoes continuous updates and testing to ensure reliability and effectiveness. The deployment of the system includes converting existing documents into PDF format, which is stored securely within the system. External Interface Requirements: The system’s interfaces are designed to be intuitive and user-friendly, facilitating ease of use for both administrators and staff members. The web-based interface is responsive and can be accessed across various devices, providing flexibility and convenience for users. Administrators have full control over system settings and user permissions, while staff members can conduct searches and access documents as permitted. Other Nonfunctional Requirements: The RBGS (Recoletos de Bacolod Graduate School) Docuware: e-Document Management System was evaluated based on attributes such as security, performance, usability, and reliability. The system received high marks for effectively meeting the graduate school’s document management needs. Regular monitoring and logging, including audit trails of user activities, help maintain the system’s integrity and security. A sample group of users provided feedback on the system’s usability, which was overwhelmingly positive, confirming that the system meets its intended purpose.